Improving the Taste of Robusta Coffee by Fermentation with Yeast Inoculum and Its Effect on Caffeine Content - Hani Fildzah Nadya; Usman Ahmad; Samsudin Samsudin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Harvesting coffee process by farmers generally executed entirety, resulting rainbow harvest. Coffee fermentation with yeast starter cultures Saccharomyces cerevisiae Y612, Candida parapsilosis Y207 and Torulospora delbrueckii Y594 was executed separately to determine the role of starter cultures on caffeine and robusta coffee taste at different maturity levels. The study was conducted at the Indonesian Industrial and Beverage Crops Research Institute in Sukabumi,, from June to November 2022. The experiment used a factorial complete randomized design. The first factor was the maturity level of the coffee and starter culture as the second factor. Fermentation was implemented for 48 hours inoculated with 108 cells/mL starter culture. The results showed that the temperature fluctuated, the pH value always decreased to 4.50 and T. delbrueckii was the starter culture with the highest activity during fermentation. Inoculum-fermented robusta coffee caffeine content was higher than non-inoculum. The lowest caffeine content was found in spontaneously fermented red fruit of 1.39%, while the highest caffeine content was produced by red fruit samples inoculated with C. parapsilosis of 2.7%. Robusta coffee with S. cerevisiae inoculation brought the best taste of robusta coffee with 82.10%, there was no significant difference between the red harvest coffee fruit and the fermented rainbow color with a starter culture. Keywords: Caffeine, Harvest, Inoculation, Maturity level, Starter cultures